Second Trimester Heterotopic Triplet Pregnancy with Intrauterine Twin Pregnancy and Ruptured Interstitial Pregnancy: A Maternal Near-Miss Case Report - Charles Nkurunziza; Theogene Rurangwa; Vincent Ngendahimana; Urania Magriples (Case Reports in Obstetrics and Gynecology)
Heterotopic pregnancy is defined as the occurrence of simultaneous intrauterine and extrauterine pregnancies. It is a rare, potentially life-threatening condition and infrequent in natural conceptions. Here, we report a case of spontaneous heterotopic triplet pregnancy with ruptured cornual ectopic pregnancy and simultaneous twin intrauterine pregnancies at 18 weeks of gestation. The event led to miscarriage of all fetuses from both the ectopic and the intrauterine twin pregnancies.